Fuel subsidy removal and welfare of the working class in Nigeria: Policy options for the state - Oladimeji, Lawal Abdullahi; Umar, Mahmoud (Journal of Social Sciences and Management Studies, 2024)
Subsidy provisioning has been a feature of market economies around the World since the end of the Second World War. In Nigeria, and other Third World countries, subsidy provision is a major instrument by which Government attempts to enhance the welfare of the masses. Over the years, successive governments in Nigeria have attempted to keep the prices of certain commodities affordable by providing one form of subsidy or the other. The Premium Motor Spirit (PMS) popularly known as Petrol in Nigeria is one of the commodities covered by subsidy until 29th May, 2023 when the newly inaugurated President Ahmed Bola Tinubu in his inaugural speech declared an end to it. A major consequence of the removal of the fuel subsidy is the cut-throat pricing of PMS throughout the country. This paper attempts to interrogate the effect of fuel subsidy removal on the welfare of the working class in Nigeria with a view to ascertaining available policy options for the State. The paper adopts the neo-classical economic theory of government policy and argues that a fundamental responsibility of the State is the protection of the welfare of the citizenry through its various policy decisions. Relying on documentary evidence, the paper found that the removal of fuel subsidy has worsened the living conditions of the working class as not only do workers now have to pay more for fuel; the multiplier effect of a continuous rise in prices of PMS on other basic necessities has made life unbearable. Consequently, the paper suggests a novel approach to the conundrum where in the Federal Government would ensure domestic refining of crude oil for local consumption or reach an understanding with other countries for a non-commercial refining of crude oil for the country.